Legal Certainty on Personal Data Protection After the Ratification of Law Number 27 2022 (Open Society Conference, 2023)
Millions of personal data spread and traded online have become a proof of the failure of data protection. Personal data leaks from online application users, health insurance participants to election participants, which when converted into economic value is quite fantastic. This raises the question of how personal data in Indonesia? How can Law Number 27 of 2022 on Personal Data Protection (UU PDP) protect personal data? By using the PDP Law legislation in comparison with other secondary legal materials, through normative legal research, with a statutory approach, these complex questions will be discussed. The 1945 Constitution of the Republic of Indonesia is a juridical basis for the formation of the PDP Law, one of which is as stated in Article 28G paragraph (1) which states that, "Everyone has the right to protection of self, family, honor, dignity, and property under his control, and is entitled to a sense of security and protection from threats of fear to do or not to do something that is a human right. While the PDP Law recognizes the rights of personal data subjects, it also introduces the terms "Personal Data Controller" and "Personal Data Processor" and regulates the scope of obligations of these two legal subjects. As a lex specialis law, UU PDP can serve as a legal foundation for personal data protection.